2008
DOI: 10.1007/s00128-008-9359-z
|View full text |Cite
|
Sign up to set email alerts
|

Dissipation and Residue of S-metolachlor in Maize and Soil

Abstract: The purpose of this article was to establish a simple residue analysis method for S-metolachlor in maize and to study its dissipation and residue in maize field eco-system. The results showed that S-metolachlor declined rapidly in maize seedling and soil after application. The half-lives of S-metolachlor in maize seedlings in Beijing and Changchun were 6.68 and 4.85 days, respectively, and in soil were 12.81 and 14.81 days, respectively. The terminal residues of S-metolachlor in soil samples were very low (aro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 11 publications
1
9
1
Order By: Relevance
“…The DT 50 value for the dissipation of S-metolachlor in soil and maize for the first-order kinetics was within the same range as that reported by Caracciolo et al (2005). In our study, the following values were reported: 11.1–14.7 days (soil) and 9.6–13.9 days (maize), while S-metolachlor half-lives in maize in Changchun and Beijing lasted longer: 6.68 and 4.84 respectively (Cao et al 2008). …”
Section: Resultssupporting
confidence: 50%
See 1 more Smart Citation
“…The DT 50 value for the dissipation of S-metolachlor in soil and maize for the first-order kinetics was within the same range as that reported by Caracciolo et al (2005). In our study, the following values were reported: 11.1–14.7 days (soil) and 9.6–13.9 days (maize), while S-metolachlor half-lives in maize in Changchun and Beijing lasted longer: 6.68 and 4.84 respectively (Cao et al 2008). …”
Section: Resultssupporting
confidence: 50%
“…Due to its cultivation in monoculture, more and more frequently, it decreases its yields owing to weed infestation, which at the early stages of growth competes with maize for nutrients and water (Sun et al 2013; Cao et al 2008). To prevent it, one uses herbicides, which play a key role in the maize conservation programmes.…”
Section: Introductionmentioning
confidence: 99%
“…Considering both soils together (Table ), the half‐life at 0 to 5 cm was 82 d, increasing to 103 d in the A 1 layer, 123 d in the B horizon, and 134 d in the C horizon (Figure ). Values obtained in the present study for the A horizon (A 0 + A 1 ) were substantially greater than half‐lives reported by others for S‐metolachlor in soils sampled from the surface 30 cm. However, other authors working with metolachlor obtained DT50 values similar to the results obtained in the present study.…”
Section: Resultscontrasting
confidence: 71%
“…Additionally, the sorghum plants can degrade the herbicide via oxidation or the glutathione-S-transferase (GST) (SLABA et al, 2015), reducing the toxicity of these plants at 28 DAA. Corn plants that absorbed 0.025 mg kg-1 Smetolachlor were able to degrade 80% of this herbicide in 10 days (CAO et al, 2008).…”
Section: Resultsmentioning
confidence: 99%